Analyzing Time Use by Occupation Area between Weekdays and Weekends by Gender of Parents in Single-Parent Families - Woo-Hyuk Jang; Jin-Hyuk Bang (Occupational Therapy International, 2023)
Introduction. Based on the “2019 Living Time Survey” data conducted by the National Statistical Office, this study is aimed at comparing the time usage of single-parent families by classifying the occupation area based on the fourth edition of the occupational therapy practice framework (OTPF) and dividing time use according to weekdays and weekends and by gender. Methods. After extracting the subjects who were selected belonging to a single-parent family from the original data of the “2019 Living Time Survey,” 404 subjects who were single parents were selected, and the data were analysed. The sample consisted of 134 males and 270 females. The time usage by occupation area during weekdays and weekends and according to the gender of the subjects was checked. By using SPSS 25.0 version for data analysis, the general characteristics and time usage of subjects were presented as frequency analysis and technical statistics, and an independent sample t-test was conducted to compare time usage on weekdays and weekends. Results. Subjects spent more time on “education” and “work” on weekdays, and on weekends, they spent more time on “activities of daily living,” “rest and sleep,” “leisure,” and “social participation.” After classifying the subjects by gender, men spent more time on “work” on weekdays, and on weekends, they spent more time on “activities of daily living,” “rest and sleep,” “leisure,” and “social participation.” Women spent more time on “education” and “work” on weekdays, and on weekends, they spent more time on “rest and sleep,” “leisure,” and “social participation.” Conclusion. By examining the time usage of single-parent families according to the day of the week, we hope that it will be used as basic data to suggest in which areas they have difficulty managing time, depending on the day of the week, and to establish solutions to insufficient time use due to gender differences.